2020
DOI: 10.3390/en13030526
|View full text |Cite
|
Sign up to set email alerts
|

Testing Non-Linear Nexus between Service Sector and CO2 Emissions in Pakistan

Abstract: Our pioneer study is aimed at investigating the role of the service sector in affecting sustainable environment in Pakistan. Using time series data over 1971–2014 and applying an autoregressive distributive lag (ARDL) model with structural break analysis, we establish a long-term equilibrium relationship of carbon dioxide (CO2) emissions with energy consumption, income level, services and trade openness. Our findings support a service-induced environmental Kuznets curve (EKC) hypothesis in Pakistan. The income… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 83 publications
5
18
0
Order By: Relevance
“…The coefficient of TOP signifies that the level of CO 2 emissions raises by 0.0208% due to a 1% increase in TOP. The results of TOP is congruent to the outcomes of Danish et al [35] and Hashmi et al [96]; they confirm the existence of a significant association between TOP and CO 2 emissions. The outcomes for 47 emerging economies can be vindicated that the size of economic growth is expanding through scale effect, which may raise the deterioration of the environment.…”
Section: Empirical Results and Discussionsupporting
confidence: 86%
“…The coefficient of TOP signifies that the level of CO 2 emissions raises by 0.0208% due to a 1% increase in TOP. The results of TOP is congruent to the outcomes of Danish et al [35] and Hashmi et al [96]; they confirm the existence of a significant association between TOP and CO 2 emissions. The outcomes for 47 emerging economies can be vindicated that the size of economic growth is expanding through scale effect, which may raise the deterioration of the environment.…”
Section: Empirical Results and Discussionsupporting
confidence: 86%
“…Based on the results of the estimation, initially, the service output proxy by the services value-added was found to positively influence the CO 2 emissions and later reduced as there was an increase in the service sector as indicated by the inclusion of the square term of services value-added. This finding is similar to Hashmi et al (2020) and Taghvaee and Parsa (2015). Although our result asserted the existence of an inverted-U shaped between the services value-added and CO 2 emissions, as the service sector grows, the later phase of the services sector will rebound the e CO 2 missions.…”
Section: Discussionsupporting
confidence: 91%
“…In single country studies, Alam (2015) deduced that the services sector intensify the CO 2 emissions in Bangladesh, India, Nepal, and Sri Langka, while Okamoto (2013) and Li et al (2017) argues that tertiarisation will reduce CO 2 emissions. These studies did not explicitly examine the EKC hypothesis unlike Hashmi et al (2020) who corroborated the subsistence of an inverted U-shaped in Pakistan. Withal, CO 2 emissions are global which indicates that there is a possibility that CO 2 emissions country spreads to another country especially within the same region due to the globalisation process and trade openness (Sohag et al 2017).…”
Section: Introductionmentioning
confidence: 97%
“…The study of for Indonesia also found that an upsurge in GDP triggers environmental degradation. Similarly, Hashmi et al (2020) contemplated that trade openness positively influences the environment in the short and long run by using the ARDL model for Pakistan over 1971-2014.…”
Section: Literature Reviewmentioning
confidence: 99%